2015
DOI: 10.1002/hed.24322
|View full text |Cite
|
Sign up to set email alerts
|

ABCLOVE: Voice therapy outcomes for patients with head and neck cancer

Abstract: The ABCLOVE voice program provides clinicians with an effective and reproducible method for voice rehabilitation in patients with head and neck cancer. © 2015 Wiley Periodicals, Inc. Head Neck 38: E1810-E1813, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Ten studies examined the impact of rehabilitation interventions on the primary outcome of communication. Six studies (60%)--5 RCTs and 1 single arm trial--identified statistically significant improvements in communication and all were conducted in those with head and neck cancer [342][343][344][345][346][347][348] (n=6). All cancer stages were represented across the seven trials, and all were conducted in a clinic or hospital system-based settings in the survivorship post-active cancer treatment phase.…”
Section: Communicationmentioning
confidence: 99%
“…Ten studies examined the impact of rehabilitation interventions on the primary outcome of communication. Six studies (60%)--5 RCTs and 1 single arm trial--identified statistically significant improvements in communication and all were conducted in those with head and neck cancer [342][343][344][345][346][347][348] (n=6). All cancer stages were represented across the seven trials, and all were conducted in a clinic or hospital system-based settings in the survivorship post-active cancer treatment phase.…”
Section: Communicationmentioning
confidence: 99%
“…Voice dysfunctions such as dysphonia are one of the main communication alterations (5) , affecting up to 50.5% of people undergoing supracricoid laryngectomy (6) , up to 37% treated with thyroidectomy (7) and up to 32% of those who received chemoradiotherapy. Voice problems can affect QoL (8) and have been associated with higher levels of depression, anxiety and distress (9)(10)(11) , so adaptive coping strategies can benefit the emotional well-being of H&N cancer patients.…”
Section: Introductionmentioning
confidence: 99%